Opferorientierung im Strafvollzug - Höffler, Katrin; Jesse, Christiane; Bliesener, Thomas (Universitätsverlag Göttingen, 2019)
The feeling of grief and other emotions victims of a crime may face are not limited to certain stages in the criminal proceeding and do not necessarily end with conviction and imprisonment of the offender. Disregarding the needs of the victim, the German penal system generally focuses only on offenders and the need to reintegrate them into society. By implementing laws concerning restorative justice programs in the prison system the German legislator seeks to dissolve this apparent contradiction. During this international conference both practitioners and scholars depicted existing restorative justice programs and outlined their legal framework. It became apparent that the reintegration of criminal offenders and additional considerations of victim interests do not necessarily exclude each other but, to the contrary, may even complement one another.